Architecture drawing of main entrance (RFA-524_Rev K) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture; Web Structures (2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF & DWG version of drawings.